Constructing a scale of defeatist personality among football players (Texas Journal of Multidisciplinary Studies, 2025)
This research aims to build a scale for the defeatist personality among football players, by identifying the psychological dimensions associated with defeatist behavior, and designing a measurement tool that has validity and reliability. The scale was developed based on a review of psychological and sports literature, and applied to a sample of players to test its accuracy and effectiveness. The results showed that the proposed scale has a high level of validity and reliability, making it a reliable measurement tool for studying the defeatist personality among players. The research recommends the necessity of using this scale in sports circles to identify players who are prone to defeatism and to work on developing psychological programs to enhance self-confidence and the ability to deal with sports pressures